Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Pada Coffee Shop Pekanbaru - Anggi Wiyani Putri; Lie Othman (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study obtained with the goal to determine the impact of service quality and also price on customer satisfaction at Recaffee Platinum. The method used in this study is quantitative analysis. The size of the sample for this study was 99 respondents, selected using accidental sampling and a questionnaire as the data collection instrument, which was statistically tested with the support by SPSS 30. The data analysis revealed that service quality (X1) significantly influences customer satisfaction (Y), price (X2) significantly influences customer satisfaction (Y), and service quality (X1) and price (X2) simultaneously significantly influence customer satisfaction (Y) at Recaffee Platinum.